The Responsibilities of Muslim Women in Dealing with Security Challenges in Nigeria - Rafatu Abdulhamid (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
The issue of insecurity has remained the most challenging problem in the world including Nigeria. In Nigeria, reports of kidnapping, armed robbery, assassination and killing/bombing which lead to lost of lives and destruction of properties kept on featuring in our media channels. In addition, women are the most vulnerable of this insurgency. They have been killed, widowed, raped or kidnapped etc. It is however to be noted that given the broader perspective of national security, government security agencies, nongovernmental organizations, Muslims both men and women, Islamic Scholars, youths etc. All should play the vital role of maintaining peace and curtailing insecurity in Nigeria. Therefore, everybody has a role to play at enhancing the national security. Islam being a comprehensive system of life provides preventive measures to curb insecurity in human society. This paper therefore examines the responsibility of the Muslim women in curbing insecurity in Nigeria. The paper observes that the causes of insecurity in Nigeria include; corruption, erosion of virtues and moralities values, youth unemployment, ignorance misuse of Islamic knowledge, globalization etc. This study uses the librarian research in which both primary and secondary sources were utilized for the work. These comprise of Qur’an, Hadith and other literatures. The result of research found that Muslim women by their pedigree and character have the potential to ensure security in the society through good child upbringing, God consciousness, acquiring true Islamic knowledge to mention a few. It concludes that if these measures are implemented, they will go a long way in arresting this quagmire of insecurity in our society.